Improving the Quality of Provided Care: Lessons Learned From Auditing Neonatal Stabilization - den Boer, Maria C.; Martherus, Tessa; Houtlosser, Mirjam; Root, Laura; Witlox, Ruben S. G. M.; te Pas, Arjan B. (Frontiers in Pediatrics, 2020)
Video and physiological parameters recording of neonatal stabilization was implemented at the Neonatal Intensive Care Unit (NICU) of the Leiden University Medical Center. In order to improve documentation and the quality of care provided during neonatal transition, we implemented weekly plenary audits reviewing recordings of neonatal stabilization in 2014. In audits, provided care is reviewed, discussing, amongst others, mask technique, compliance to the prevailing local guideline, and clinical decision-making and alternative treatment options. In this perspective, we argue that auditing neonatal stabilization is a valuable tool to improve patient safety and the quality of care provided during neonatal stabilization. We therefore report lessons learned and areas for improvement that could be identified and addressed during audits conducted at our NICU. Important areas for improvement were guideline compliance, documentation, the usage of medical devices, the conduct of delivery room studies and clinical decision-making. By reporting our experiences we hope to encourage other NICUs to also implement regular audit meetings, fitting to their improvement needs.